Late skin fibrosis in systemic sclerosis: a study from the EUSTAR cohort. (22nd June 2022) - Hughes, Michael; Huang, Suiyuan; Alegre-Sancho, Juan Jose; Carreira, Patricia E; Engelhart, Merete; Hachulla, Eric; Henes, Joerg; Kerzberg, Eduardo; Pozzi, Maria Rosa; Riemekasten, Gabriela; Smith, Vanessa; Szücs, Gabriella; et al.
Abstract: Objectives: The early trajectory of skin fibrosis provides insights into the disease course of systemic sclerosis (SSc) including mortality; however, little is known about late skin fibrosis. The aims of our study were to ascertain the prevalence and characteristics of late skin fibrosis in SSc. Methods: We developed and tested three conceptual scenarios of late (>5 years after first non-RP feature) skin fibrosis including new worsening of skin disease, and failure to improve after worsening within 5-year window. We defined skin worsening as change in modified Rodnan skin score (mRSS) ≥5 units or ≥25%. Using strict inclusion criteria including complete mRSS, we identified 1, 043 (out of 19 115) patients within the EUSTAR database for our analysis. We further restricted analysis within 887 (out of 1043) patients who had lcSSc or dcSSc at baseline. Results: One-fifth of patients among the whole cohort ( n  = 208/1043, 19.9%) experienced mRSS worsening, including in patients with lcSSc or dcSSc at baseline ( n  = 193/887, 21.8%). This was largely due to new skin worsening after the 5-year window or failure to improve with worsening within the 5-year window. Patients with lower baseline mRSS and lcSSc were more likely to develop late skin fibrosis. Anti-Scl-70 was associated with progression from baseline lcSSc to dcSSc, and anticentromere was protective. Conclusions: Late skin fibrosis is not uncommon in SSc. We have identified different patterns relevant to clinical practice and trial design. Late skin fibrosis is a neglected manifestation of SSc and warrants further investigation including to determine clinical outcomes and optimal therapeutic strategy.